A Randomized Controlled Trial of Positioning for Lumbar Puncture in Young Infants. Issue 8 (August 2016) - Hanson, Amy L.; Schunk, Jeff E.; Corneli, Howard M.; Soprano, Joyce V.
Abstract : Objective: The lateral and sitting positions are those most widely used to perform lumbar puncture (LP) in infants. This study sought to compare LP success rates by position. Secondary outcomes were successful LP on the first attempt and rates of procedural complications. Methods: Infants aged 1 to 90 days undergoing LP in our pediatric emergency department between June 1, 2012 and October 31, 2013 were randomized to 1 position or the other. Successful LP was defined as collection of cerebrospinal fluid with a red blood cell count of less than 10, 000 cells/mm 3 on either of the first 2 attempts. Electronic medical records were reviewed for patient information, cerebrospinal fluid results, and procedural complications. Providers completed a questionnaire detailing their previous LP experience and technique. Primary results were analyzed using the intention-to-treat principle. Results: We enrolled 168 infants. Of 167 with data eligible for analysis, 82 (49%) were randomized to the lateral position. There was no statistically significant difference in LP success rate between the lateral (77%, 63/82) and sitting (72%, 61/85) positions (difference, 5.1%; 95% confidence interval, −8.2%–18.3%). There were no significant differences in success on the first LP attempt or the rates of procedural complications. Conclusions: Among infants 1 to 90 days of age, this study found no difference in LP success between the lateral and sitting positions.